2020
DOI: 10.1038/s41598-020-63670-9
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of female and male Aedes aegypti from discarded container habitats using a stable isotope mark-capture study design in South Texas

Abstract: Aedes aegypti is the main vector of arboviral diseases such as dengue, chikungunya and Zika. A key feature for disease transmission modeling and vector control planning is adult mosquito dispersal. We studied Ae aegypti adult dispersal by conducting a mark-capture study of naturally occurring Ae. aegypti from discarded containers found along a canal that divided two residential communities in Donna, texas, USA. Stable isotopes were used to enrich containers with either 13 c or 15 n. Adult mosquitoes were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…This was done to account for the effect of AGO coverage (measured as the number of traps and houses within an area based on the dispersal of female Ae. aegypti [38]) during the intervention periods (August to December), since it has been observed that these traps modulate the abundance of female Ae. aegypti [39].…”
Section: Discussionmentioning
confidence: 99%
“…This was done to account for the effect of AGO coverage (measured as the number of traps and houses within an area based on the dispersal of female Ae. aegypti [38]) during the intervention periods (August to December), since it has been observed that these traps modulate the abundance of female Ae. aegypti [39].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, non-experimental households were inter-dispersed between the experimental households, and then possibly the unexposed males migrated to adjacent non-experimental households, which were not surveyed by human landing collections and therefore must be examined in future studies. Last, in a recent study conducted approximately at 15 km (in USA, across the border) from this study site, examined larvae marked with isotopes in tires that produced males collected in BG Sentinel traps at 220 m ( Juarez et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both sexes of Ae. aegypti typically disperse less than this and most estimates suggest 150-250 m is typical [123][124][125][126].…”
Section: Release Locationsmentioning
confidence: 99%